Perancangan Automatic Transfer Switch (ATS) Pembangkit Listrik Hybrid Panel Surya dan Generator untuk Bagan Apung - Aswar, Muhammad Baharuddin Arif; Mahmuddin, Faisal; Lestari, Anugrah Darma (Center of Techonolgy (COT), Fakultas Teknik, Universitas Hasanuddin, 2021)
Design of Automatic Transfer Switch (ATS) Hybrid Solar Panel and Generator Power Plant for Floating Fishnet. Fishing business with floating nets has great benefits for small-scale fisheries. The development of the floating fishnet is quite good in Indonesia, especially in terms of production and fishing production. The problem of lack of lighting sources is the main problem faced by fishermen on the floating fishnet because the source of electricity used usually comes from conventional power plants (gasoline generators). Hybrid power plant is one of the power plant innovations that can take advantage of the use of renewable energy and become a solution to produce alternative energy on a floating fishnet. Automatic Transfer Switch (ATS) of hybrid power generation system is designed for automatic switch when the main power generation system has reached the specified voltage limit of 11V and is also designed for automatic switch when the backup power generation system has reached the specified voltage limit of 10V. The results obtained indicate that the main power generation source supplies 240W of load for 44 minutes with an average consumption current of 0.182A, while the backup power source supplies 240W for 28 minutes with an average current of 0.177A.